Mortality in children with complicated severe acute malnutrition is related to intestinal and systemic inflammation: an observational cohort study - Attia, Suzanna; Versloot, Christian J; Voskuijl, Wieger; van Vliet, Sara J; Di Giovanni, Valeria; Zhang, Ling; Richardson, Susan; Bourdon, Céline; Netea, Mihai G; Berkley, James A; van Rheenen, Patrick F; Bandsma, Robert HJ (The American journal of clinical nutrition, 2016)
Diarrhea affects a large proportion of children with severe acute malnutrition (SAM). However, its etiology and clinical consequences remain unclear. We investigated diarrhea, enteropathogens, and systemic and intestinal inflammation for their interrelation and their associations with mortality in children with SAM. Intestinal pathogens (n = 15), cytokines (n = 29), fecal calprotectin, and the short-chain fatty acids (SCFAs) butyrate and propionate were determined in children aged 6-59 mo (n = 79) hospitalized in Malawi for complicated SAM. The relation between variables, diarrhea, and death was assessed with partial least squares (PLS) path modeling. Fatal subjects (n = 14; 18%) were younger (mean ± SD age: 17 ± 11 compared with 25 ± 11 mo; P = 0.01) with higher prevalence of diarrhea (46% compared with 18%, P = 0.03). Intestinal pathogens Shigella (36%), Giardia (33%), and Campylobacter (30%) predominated, but their presence was not associated with death or diarrhea. Calprotectin was significantly higher in children who died [median (IQR): 1360 mg/kg feces (2443-535 mg/kg feces) compared with 698 mg/kg feces (1438-244 mg/kg feces), P = 0.03]. Butyrate [median (IQR): 31 ng/mL (112-22 ng/mL) compared with 2036 ng/mL (5800-149 ng/mL), P = 0.02] and propionate [median (IQR): 167 ng/mL (831-131 ng/mL) compared with 3174 ng/mL (5819-357 ng/mL), P = 0.04] were lower in those who died. Mortality was directly related to high systemic inflammation (path coefficient = 0.49), whereas diarrhea, high calprotectin, and low SCFA production related to death indirectly via their more direct association with systemic inflammation. Diarrhea, high intestinal inflammation, low concentrations of fecal SCFAs, and high systemic inflammation are significantly related to mortality in SAM. However, these relations were not mediated by the presence of intestinal pathogens. These findings offer an important understanding of inflammatory changes in SAM, which may lead to improved therapies. This trial was registered at www.controlled-trials.com as ISRCTN13916953.